A new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Cerrado-Amazonian forest transition zone, Brazil - Raimundi, Erikcsen A.; Cabette, Helena R. S.; Brasil, Leandro S.; Salles, Frederico F. (Zootaxa, 2017)
A new species of Miroculis is described based on all developmental stages (nymph, and male and female imagos). Miroculis yulieae sp. nov. is recorded from the transitional area of Cerrado-Amazonia, Brazil.